Analisa Efisiensi Pada Transformator Daya 60 MVA Di Gardu Induk Babadan Sidoarjo - Ricky Markus Solossa; Hadi Tasmono (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Larger and better-quality electricity will be needed due to the increased economic growth of the industrial sector and the development of the city of Surabaya, especially in the Sidoarjo region. One of the devices whose efficiency needs to beined in order to be able to conduct electricity sustainably is a transformer. The transformer that is often installed on the Mainstream or Distribution Guard, serves as a step-up and step-down transformer in power transmission. There were losses in the transformer from the current flowing through the copper wire, losses on the reverse flow of the iron core, and damage from the torque of the current on the iron kernel which caused the transformator to become less efficient. That's why the author took the title